Rewriting medieval French literature studies in honour of Jane H.M. Taylor - Tether, Leah ca. 20./21. Jh; Busby, Keith (De Gruyter, 2021)
Jane H. M. Taylor is one of the world's foremost scholars of rewriting or réécriture. Her focus has been on literature in medieval and Renaissance France, but rewriting, including continuation, translation, and adaptation, lies at the heart of literary traditions in all vernaculars. This book explores both the interdisciplinarity of rewriting and Taylor's remarkable contribution to its study. The rewriting and reinterpretation of narratives across chronological, social and/or linguistic boundaries represents not only a crucial feature of text transmission, but also a locus of cultural exchange. Taylor has shown that the adaptation of material to conform to the expectations, values, or literary tastes of a different audience can reveal important information regarding the acculturation and reception of medieval texts. In recent years, numerous scholars across disciplines have thus turned to this field of enquiry. This collection of studies dedicated to the rewriting of medieval French literature from the twelfth to the twenty-first centuries by Taylor's friends, colleagues, and former students offers not only a fitting tribute to Taylor's career, but also a timely consolidation of the very latest research in the field, which will be vital for all scholars of medieval rewriting. With contributions from Jessica Taylor, Keith Busby, Leah Tether, Logan E. Whalen, Mireille Séguy, Christine Ferlampin-Acher, Ad Putter, Anne Salamon, Patrick Moran, Nathalie Koble, Bart Besamusca, Frank Brandsma, Richard Trachsler, Carol J. Chase, Maria Colombo Timelli, Laura Chuhan Campbell, Joan Tasker-Grimbert, Jean-Claude Mühlethaler, Michelle Szkilnik, Thomas Hinton, Elizabeth Archibald
Keywords: Taylor, Jane H. M. -- 1941-; Geschichte; Geschichte 1000-1500; Mittelalterliche Literatur; Renaissance; Rewriting; Rezeption; LITERARY CRITICISM / European / French; French literature -- To 1500 -- History and criticism; Bearbeitung; Französisch; Literatur; Festschrift; Aufsatzsammlung